A case for closed-loop recycling of post-consumer PET for automotive foams. (January 2018) - Bedell, Matthew; Brown, Matthew; Kiziltas, Alper; Mielewski, Deborah; Mukerjee, Shakti; Tabor, Rick
Highlights: Mixed polyethylene terephthalate (PET) waste streams can be up-cycled into polyols. Synthesis of flexible polyurethane foams from these PET polyols is demonstrated. Automotive-relevant mechanical/thermal properties increase with PET polyol content. The results demonstrate a closed-loop opportunity for automotive interior foams. Abstract: Striving to utilize sustainable material sources, polyester polyols made via glycolysis and esterification of recycled polyethylene terephthalate (rPET) scrap were used to synthesize flexible polyurethane (PU) foams typically found in automotive interior applications. The objective of this endeavor was to ascertain if a closed-loop model could be established with the discarded PET feedstock. In five separate formulations, up to 50% of the total polyol content (traditionally derived from petroleum-based feedstock) was replaced with the afore-mentioned sustainable recycled polyols. These foams underwent mechanical, thermal, morphological, and physical characterization testing to determine feasibility for use in an automotive interior. Young's modulus, tensile stress at maximum load, tear resistance, and compression modulus all increased by combined averages of 121%, 67%, 32%, and 150% over the control petroleum-based formulation, respectively, in foams possessing 50% rPET polyol content. Thermal stability also increased with sustainable polyol content; thermogravimetric analysis showed that 50% mass loss temperature increased by an average of 20 °C in foams containing 30% recycled polyol. Properties of density and SAG factor remained within 5% of the control petroleum-based reference foams. After comparing these findings to traditional polyols, a compelling argument can be made for the use of post-consumer automotive and industrial feedstocks in developing high-performing interior automotive PU foams.